Do Outstanding Employees Have More Responsibility in the Hotel? A Case Study in Moderation Effect Model at XYZ Hotel - Adnyana, I Made Sucipta; Santi Diwyarthi, Ni Desak Made; Wiartha, Nyoman Gede Mas; Ariasri, Nyoman Reni; Jata, I Wayan (Westscience Press, 2024)
This study aims to analyze the relationship between educational background, work experience, and employee performance in the Room Division Department, consisting of 55 employees, 30 of whom are categorized as outstanding employees. The research examines the role of education and experience in exceptional performance and identifies key indicators of high-performing employees, such as high dedication, strong problem-solving abilities, initiative, and teamwork. The results show that employees with higher education and experience tend to exhibit outstanding performance, supporting human capital and job performance theories. This study contributes new insights into the diversity of backgrounds and optimal performance in the hospitality industry.